The Impact of the Covid 19 Pandemic on Facilities Providers and Sports Activities in Palu City (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The motivation for this research is the impact of the COVID-19 pandemic on sports facilities and activities. Objectives 1) Analyze the status of business actors supplying sports facilities 2) Analyzing the challenges faced by commercial actors in the provision of sports facilities 3) Analyzing corporate actors' solutions for providing sporting facilities in the city of Palu. This study used a qualitative research design to investigate phenomenology. This study uses the Palu City Diaspora, sports facilities business actors, and the community as its data sources. Data collection techniques was using observation, interviews and documentation. The four interacting components of data analysis were data collection, data reduction, data display, and conclusion. This study's conditions pertain to the state of sports, particularly the availability of sports facilities and activities. The impact of the COVID-19 pandemic is felt not only by the community as sports players, but also by the government, particularly commercial actors providing sports facilities. Constraints The inability of business actors providing sports facilities and activities to operate is mostly caused by the closure of sports facilities and infrastructure in Palu City. During the covivirus 19 pandemic, the answer for facility business actors through internet media can help in marketing the rental of sports facilities or services. The research concludes that the condition of sports facilities business actors during the covid 19 pandemic has resulted in a decrease in income. Always improve by creating health measures so that their businesses can reopen throughout the transition from the covid 19 pandemic.